Are Current Technical Exclusion Criteria for Clinical Trials of Magnetic Resonance–Guided High‐Intensity Focused Ultrasound Too Restrictive?: Early Experiences at a Pediatric Hospital. (30th March 2020) - Lau, Lung W.; Eranki, Avinash; Celik, Haydar; Kim, AeRang; Kim, Peter C. W.; Sharma, Karun V.; Yarmolenko, Pavel S.
Abstract : Certain technical criteria must be met to ensure the treatment safety of magnetic resonance–guided high‐intensity focused ultrasound. We retrospectively reviewed how our enrollment criteria were applied from 2014 to 2017 in a clinical trial of magnetic resonance–guided high‐intensity focused ultrasound ablation of recurrent malignant and locally aggressive benign solid tumors. Among the 36 screened patients between 2014 and 2017, more than one‐third were excluded for technical exclusion criteria such as the anatomic location and proximity to prosthetics. Overall, patients were difficult to accrue for this trial, given the incidence of these tumors. To increase potential accrual, screening exclusion criteria could be more generalized and centered on the ability to achieve an acceptable treatment safety margin, rather than specifically excluding on the basis of general anatomic areas.